IMPLEMENTATION OF RISK MANAGEMENT IN PRIVATE UNIVERSITY - Indra P, I Made (Yayasan Education and Social Center, 2024)
Risk management plays a vital role in the sustainability of modern institutions, and it has been implemented by various entities such as the banking sector, the business world, government, and universities. Risk management is essential. So that risk management can be carried out, a method is needed to overcome it. One method that can be used is the International Organization for Standardization (ISO) 31000. This research will be carried out at the STMA Trisakti Campus, which is one of the largest universities in Indonesia and is managed by the Trisakti Foundation, which has six educational units. The effectiveness of implementing risk management at the Trisakti Campus still needs to be debated, considering the various challenges and obstacles faced by private universities in implementing a comprehensive risk management system. This research aims to analyze risk identification, risk analysis and risk evaluation at STMA Triskati. The research uses a qualitative method with a risk management approach. Interviews were conducted with informants from leadership, study program managers, quality assurance, lecturers and students. The research results obtained six priority risks which fall into the high-risk category, namely: risk of decreasing research quality, risk of not meeting the number of publications, risk of reducing the number of students, risk of financing capacity, and risk of lowering the quality of administrative services.